Odpowiedzi

Najlepsza Odpowiedź!
2009-11-19T20:57:17+01:00
A) 8x - 2xy
b) 2a²x
c) -5ab -a³b
d) 0,5x²y - 6,5xy²
e) 2x + 10y
f) 9a²b²
g) 36x²y²
9 3 9
2009-11-19T20:59:35+01:00
A) 3x - 2xy +5x = 8x-2xy
b) 7a² + 2a²x - 9a² + 2a²=2a²x
c) 3ab - a³b - 8ba=11ab- a³b
d) 2x²y - 3,5xy² - 1,5x²y - 3xy² + 4xy² - 4xy²=0,5x²y+0,5xy²+xy²
e) (5x-7y) - (3y-7x)=2y
f) - (a - 2b) - 2(b-2a)=3a
g)3(x-2y) - 2 (y-3x)=9x-8y
9 4 9
2009-11-19T21:05:28+01:00
A) 8x-2xy

b)2a²x

c)-5ab-a³b

d)0,5x²y-6,5xy²

e)5x-7y-3y-7x=-2x-10y

f)-a+2b-2b+4a=3a

g)3x-6y-2y+3x=6x-8y
5 4 5